2010
DOI: 10.1099/jmm.0.021816-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori dupA and gastric acid secretion are negatively associated with gastric cancer development

Abstract: Few reports have described the cancer prevalence of peptic ulcer patients with long-term followup studies. We have conducted a long-term retrospective cohort study of Japanese peptic ulcer patients and evaluated the risk factors for the occurrence of gastric cancer (GCa). A total of 136 patients diagnosed with peptic ulcers from 1975 to 1983 were enrolled. These 136 cases [102 males and 34 females; 69 gastric ulcer (GU) and 67 duodenal ulcer (DU) patients at the time of enrolment; mean follow-up period of 14.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Irregularity in meal timing possibly increases glutathione production in the stomach. In addition it may also cause low gastric acid secretion and studies have shown that clinical conditions with low gastric acid secretion are associated with increased risk of gastric cancer [35, 36]. Meal timing may also impact physiological parameters such as endocrine variables [37].…”
Section: Discussionmentioning
confidence: 99%
“…Irregularity in meal timing possibly increases glutathione production in the stomach. In addition it may also cause low gastric acid secretion and studies have shown that clinical conditions with low gastric acid secretion are associated with increased risk of gastric cancer [35, 36]. Meal timing may also impact physiological parameters such as endocrine variables [37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, among most of Asian countries, a significant association between disease development and dupA status can be reported[38,45-54]. In two studies, first by Imagawa et al[37] patients infected with dupA -positive strains showed higher risk to suffer from duodenal ulcer than dupA -negative patients. In second study, we have found that higher acid resistance of the dupA -positive strains can explain the adaptation of those strains to human stomach with high gastric acid output[35].…”
Section: Virulence Of H Pylorimentioning
confidence: 99%
“…In a retrospective cohort study from Japan including patients with peptic ulcer for a 14.4 years mean follow-up, presence of dupA was associated with lower GC incidence and lower acid output compared with dupA-negative subjects [50]. A meta-analysis on the association of dupA with different gastroduodenal diseases revealed regional differences in the related diseases.…”
Section: Role Of Bacterial and Host Factors In Gc Developmentmentioning
confidence: 99%